THE EFFECT OF INTRODUCING SUPRASEGMENTAL FEATURES TOWARDS STUDENTS’ LISTENING ABILITY - Fadilla, Suci (ELP (Journal of English Language Pedagogy), 2023)
This research aimed to address the difficulties faced by students in listening comprehension, particularly in understanding spoken vocabulary and grasping the overall meaning of audio materials. The study focused on investigating the effect of introducing suprasegmental features on students' listening ability. The significance of this research lies in its potential to enhance students' comprehension of auditory content. The research followed a pre-experimental design, specifically utilizing a pre-test and post-test approach. The participants consisted of 16 students from XII IPA at SMA N 2 Bukik Barisan. Data collection involved assessing the students' performance through pre-test and post-test scores. The intervention involved providing materials on suprasegmental features supported by audio and video. Data analysis was conducted using the t-test formula, with the obtained t-value compared to the critical t-value at a 5% significance level (?=0.05) and 15 degrees of freedom. The results revealed a significant effect of introducing suprasegmental features on students' listening ability, as the obtained t-value (2.827) exceeded the critical t-value (1.753). Moreover, the post-test scores (68.75) exhibited improvement compared to the pre-test scores (55.31). In conclusion, the findings demonstrate that the introduction of suprasegmental features positively impacted students' listening ability. The results imply that integrating suprasegmental features in teaching practices can assist students in enhancing their listening comprehension skills. Therefore, educators are encouraged to incorporate suprasegmental features to foster improved listening abilities among students.